Efektivitas Implementasi Model Pembelajaran Project Based Learning Terhadap Kreativitas Dan keaktifan Peserta dididik - Melian Umami Afah Putri; Didik Tri Setiyoko (Peneliti.net, 2022)
This research is motivated by the problems found in the field, namely the low creativity and also the activeness of students. It is proven from the results of initial observations made by researchers. The teacher does not facilitate learning that can increase the creativity and also the activeness of students, so this research is carried out. This study aims to determine the effectiveness in implementing the Project Based Learning learning model on the creativity of students and also to determine the effectiveness in implementing the Project Based Learning learning model on the activeness of students. This type of research is a quantitative experiment with a pretest posttest control group design, all fifth grade students of SD Negeri Siasem 03 are the population. The sample used is the saturated sample in this study, namely class VA (experimental class). Data collection techniques in the form of pretest posttest questions, creativity questionnaires and also student activity observation sheets. The final data analysis used is the t test. It is shown from the x-test to Y1 with significant results 0.000 <0.05 and the x-test to Y2 with the results of 0.001 <0.05 then ha of the two tests is accepted, which means that there is an effectiveness of the implementation of the Project Based Learning learning model on the creativity and activity of students.